Major Factors Affecting the Live Birth Rate After Frozen Embryo Transfer Among Young Women - Pan, Ye; Hao, Guimin; Wang, Qiumin; Liu, Hong; Wang, Ze; Jiang, Qi; Shi, Yuhua; Chen, Zi-Jiang (Frontiers in Medicine, 2020)
In recent years, the freeze-all strategy has been widely adopted and applied. However, with the exception of age, the factors that affect the outcomes of frozen embryo transfer are still unclear. Therefore, the identification and mitigation of factors that influence the live birth rate after frozen embryo transfer is a good way to increase the “take-home-baby” rate of frozen embryo transfer. The objective of this study was to identify factors affecting the live birth rate after cleavage-stage frozen embryo transfer in young ovulatory women. This was a secondary analysis from a previously published multicenter randomized controlled trial (ChiCTR-IOR-14005406) that was originally designed to compare the live birth rate and perinatal complications after fresh embryo transfer to those after frozen embryo transfer among ovulatory women. This study was carried out using a portion of the data from the original randomized controlled trial, which included 917 young women who underwent cleavage-stage frozen embryo transfer. The 16 clinical candidate variables potentially affecting the live birth rate after frozen embryo transfer were analyzed. Univariable analysis and multivariable analysis were performed to assess the relationship between predictive factors and outcomes, with the aim of identifying independent predictors of live birth after frozen embryo transfer. In this study, the live birth rate was 53.0% (486/917). Three independent predictors were ultimately identified as the main factors affecting the live birth rate of ovulatory young women. Infertility duration [odds ratio (OR): 0.933, 95% confidence interval (CI): 0.876–0.995, p = 0.033], endometrial thickness before frozen embryo transfer (OR: 3.375, 95% CI: 1.556–7.321 p = 0.002), and the number of embryos transferred (OR: 2.653, 95% CI:1.226–5,743, p = 0.013) were the major factors contributing to the live birth rate after cleavage-stage frozen embryo transfer among young women. The cut-off point for infertility duration was 4.5 years, and the cut-off point for endometrial thickness was 0.89 cm. Infertility duration, endometrial thickness and number of embryos transferred might affect the live birth rate after frozen embryo transfer among young women. This result could help inform clinical decisions and counseling to increase the live birth rate after frozen embryo transfer among young women.